2015
DOI: 10.1007/s12094-015-1332-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive biomarker candidates to delineate efficacy of antiangiogenic treatment in renal cell carcinoma

Abstract: Antiangiogenic therapy is currently considered as the cornerstone of treatment in metastatic kidney cancer. A monoclonal antibody against the vascular endothelial growth factor (VEGF) and several tyrosine kinase inhibitors targeting the VEGF receptors demonstrated, 7 years ago, to deeply impact the outcome of this tumor and became a model of integration of molecular knowledge into clinical practice. Unfortunately, no further improvement in survival has been made and 20-25 % of cases remain primary refractory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…The expression of ATAD2 in various malignant tumors is significantly higher than that in normal tissues (9), and ATAD2 has been used to evaluate the clinical prognosis of various cancers, such as lung cancer (10, 11), breast cancer (11), hepatocellular carcinoma (12), ovarian cancer (13), endometrial cancer (14) and gastric cancer (15), which are consistent with the results of ATAD2 expression in our study. Notably, we found that the expression levels of ATAD2 were up-regulated in LUAD tissues and cell lines compared to normal lung tissues and cell lines, respectively (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The expression of ATAD2 in various malignant tumors is significantly higher than that in normal tissues (9), and ATAD2 has been used to evaluate the clinical prognosis of various cancers, such as lung cancer (10, 11), breast cancer (11), hepatocellular carcinoma (12), ovarian cancer (13), endometrial cancer (14) and gastric cancer (15), which are consistent with the results of ATAD2 expression in our study. Notably, we found that the expression levels of ATAD2 were up-regulated in LUAD tissues and cell lines compared to normal lung tissues and cell lines, respectively (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…For the exploration of gene mutations, a single-arm, phase II study of apatinib in refractory metastatic colorectal cancer has analyzed a panel of 1,021 cancer-related genes by ctDNA, but has not found any positive results associated with PFS or OS 56 . One possible explanation is that by blocking VEGF signal transduction, antiangiogenic therapies act not only on tumor cells but also on the microenvironment 57 , 58 , thus making identification of a biomarker in ctDNA difficult. Our investigation revealed an association between gene alterations in ctDNA at baseline and outcomes during antiangiogenic-based therapy, thus demonstrating that clinical outcomes depend on somatic variants, in terms of both mutation burden and frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive factors, especially those related to the physiopathologic process of mRCC, could be helpful in guiding therapy for these patients. To date, plasma predictive factors have not been clearly established (18). Another point to address is the evaluation of tumor response classically based on the RECIST criteria (e.g., a decrease in the size of tumor lesions).…”
Section: Introductionmentioning
confidence: 99%